ОБҐРУНТУВАННЯ ЦІЛЬОВОГО ПРОФІЛЮ ЯКОСТІ ДЛЯ РОЗРОБКИ КОМБІНОВАНИХ ОЧНИХ КРАПЕЛЬ ДЛЯ ТЕРАПІЇ ГЛАУКОМИ - Yakubchuk, О. M.; Fetisova, O. H.; Dorovskyi, A. V.; Andryukova, L. M. (Фармацевтичний часопис, 2016)
Substantiation of a QUALITY Target PROFILE FOR THE DEVELOPMENT OF COMBINED eye drops for glaucoma treatment A.M.Yakubchuk, E.G. Fetisova, A.V.Dorovskyy, L.M. Andryukova NationalPharmaceuticalUniversity, Kharkiv. The article contains the definition of an element of pharmaceutical development, namely, the quality target profile of combined eye drops for glaucoma treatment. The feasibility of the drug developing has been scientifically substantiated by the research results of current trends in the glaucoma treatment, one of which is a combination of drugs with different mechanisms of action. The quality target drug profile has been defined in relation to quality, safety and efficacy. It forms the basis for development planning and a better understanding of the drug and the process. Substantiation of quality target profile for combined eye drops with antyglaucomous actions has been conducted for all aspects that recommended by guidelines 42-3.0:2011 «Medicinal products. Pharmaceutical development (ICH Q8)» taking into account the characteristics of the dosage form, and set consistently: the alleged use in the clinical setting, route of administration, dosage form, delivery system; strength dose; system container / closure means; quality criteria of medicinal product designated for placing on the product market. It has been substantiated intended use in a clinical setting, route of administration and dosage form with the assistance of available scientific data, information and knowledge: - Active substance Timolol maleate - adrenergic agent, is most often used at the present date as part of hypotensive drugs; Taurine refers to the substances that stabilize adrenergic receptors and can change the pharmacological activity of adrenergic drugs; - Combined use of Timolol maleate and Taurine enhances the hypotensive effect by reducing production and increasing the outflow of aqueous humor, because of pharmacological synergy action of both drugs, which provides increased outflow of aqueous humor through the drainage system of the eye; - Eye drops continue to be the most common dosage form in ophthalmology, providing local application by instillation into the eye. Regarding potency doses: active substances selected for the development of combined eye drops are well known and used as part of eye drops (mono-drugs), their therapeutic concentrations are given in the references, and for the study selected concentration of 0.34% for timolol maleate and 4% - for taurine. Planning choice of container / closure means has been made taking into account, firstly, the market experience of primary packaging for finished mono drugs of timolol and taurine, secondly, available facilities of eye drops industrial production in various primary packaging types inUkraine. Given the number of appointed drug instillation for daily glaucoma treatment (1 drop), drops weight interval for domestic production drip (25-45 mg), and the shelf life of eye drops after opening the vial (1 month) the studies have been planned in the following types of primary packaging: glass containers with nominal capacity of 5 ml closed by rubber closures and pressurized by aluminum caps; low density polyethylene containers with a capacity of 1 ml and 5 ml made by Blow-Fill-Seal packaging system; assembly low density polyethylene containers with a capacity of 5 ml. Regarding the aspect of substantiation of the drug quality criteria: the regulated indicators and the biomedical requirements were the basis. The list of biomedical monitoring indicators consists of pH, osmolarity, viscosity, refractive index. It has been applied general list of basic requirements for eye drops drug form in aqueous solution at multidose containers that developed by us based on the analysis and evaluation of the different regulations and information sources. Key words: combined eye drops, glaucoma, quality target profile, quality indexes. Literature 1. Likarsʹki zasoby. Farmatsevtychna rozrobka (ICH Q8): ST-N MOZU 42-3.0:2011. – Chastyna II: Dodatok do kerivnykh vkazivok z farmatsevtychnoyi rozrobky (ICH Topic Q 8 Dodatok do farmatsevtychnoyi rozrobky) - K. : MOZ Ukrayiny, 2011. – 33 s. – (Nastanova). 2. Derzhavnyy reyestr likarsʹkykh zasobiv Ukrayiny. - [Elektronyy resurs]. - Rezhym dostupu: - http://www.drlz.kiev.ua/ 3. Kompendyum on-line. - [Elektronyy resurs]. - Rezhym dostupu: - http://compendium.com.ua/ 4. Rehystr lekarstvennykh sredstv Rossyy®. RLS®. - [Elektronyy resurs]. - Rezhym dostupu: - http://www.rlsnet.ru/ 5. Spravochnyk Vydalʹ «Lekarstvennye preparaty v Rossyy». - [Elektronyy resurs]. - Rezhym dostupu: - http://www.vidal.ru/ 6. Ratsyonalʹnaya farmakoterapyya v oftalʹmolohyy: Ruk. dlya praktykuyushchykh vrachey / E.A. Ehorov, V.N. Alekseev, YU.S. Astakhov, V.V. Brzhevskyy, A.F. Brovkyna y dr.; pod obshch. red. E.A. Ehorova. – M.: Lytterra, 2004. – 954 s. 7. Kuroedov A.V. Perspektyvy prymenenyya kombynyrovannykh atyhlaukomnykh preparatov (obzor lyteratury) / A.V. Kuroedov // Klynycheskaya oftalʹmolohyya. – 2007. - №4. - S. 176 - 180. 8. Kuroedov A.V. Ahressyya protyv prohressyy: kak my ponymaem éffektyvnostʹ kombynyrovannykh antyhlaukomnykh preparatov (obzor lyteratury) / A.V. Kuroedov // Klynycheskaya oftalʹmolohyya. – 2008. - №4. – S. 143 -145. 9. Astakhov YU.S. Obshchye pryntsypy medykamentoznoho lechenyya zabolevanyy hlaz / YU.S. Astakhov, E.A. Ehorov, T.V. Stavytskaya // Klynycheskaya oftalʹmolohyya. – 2004. – №1. – S. 2-5. 10. Ehorov E.A. Otdelʹnye klynyko–épydemyolohycheskye kharakterystyky hlaukomy v stranakh SNH y Hruzyy. Rezulʹtaty mnohotsentrovoho otkrytoho retrospektyvnoho yssledovanyya (chastʹ 2) / E.A.Ehorov, A.V. Kuroedov // Klynycheskaya oftalʹmolohyya. – 2012. - № 1. – S. 19- 22. 11. Lombardini J.B. Effects of taurine and mitochondrial metabolic inhibitors on ATP-dependent Ca2+ uptake in synaptosomal and mitochondrial subcelluar fractions of rat retina // Neurochem. 1988. V. 51. №1. P. 200-205. 12. Duffin R.M., Christensen R.E., Bcrgamini M.V. Suppresion of adrenergic adaptation in the eye with prostaglandin synthesis inhibitor//Invest. Ophthal.VisSci. 1980. V. 21. №5. P. 756-759. 13. Maychuk YU.F. Taufon v lechenyy hlaznykh bolezney. Obzor lyteratury y sobstvennye nablyudenyya // Medytsynskye tekhnolohyy. Otsenka y vybor. - 2011. - N 1. - S.56-61. 14. Nefëdov L.Y. Tauryn (byokhymyya, farmakolohyya y medytsynskoe prymenenye). - Hrodno , 1999. - 145s. 15. Bunyn A.YA., Ermakova V.N., Babyzhaev M.A. Rezulʹtaty sochetannoho prymenenyya taufona y tymolola pry lechenyy bolʹnykh otkrytouholʹnoy hlaukomy // Vestn. oftalʹmolohyy. - 1990. - T .106, №4. - S .9 - 11. 16. Ermakova V.N. Éffektyvnostʹ sochetanyya Taufona s antyadrenerhycheskymy preparatamy pry pervychnoy otkrytouholʹnoy hlaukome // Rossyyskyy oftalʹmolohycheskyy zhurnal. - 2008. - №2.- S. 12-17. 17. Olah Z., Veselovsky J. Rabbit's intraocular pressure after instillation of timolol and aminoacid lysine, arginine, glycine or taurine mixture // Bratisl Lek Listy 2007. V. 108. №7. P. 283-286. 18. Pat. 79245 U Ukrayina. A61K9/08; A61P27/02; A61K31/00. Likuvalʹnyy helʹ dlya ochey «Tauhelʹ» / Sokolova L.V. (UA), Berdey I.I. (UA). - № u 201213798; zayavl. 03.12.2012; opubl. 10.04.2003, Byul. № 7. 19. Bestoxol (Eye Drops), World Medicine Ophthalmics - [Elektronyy resurs]. - Rezhym dostupu: - http://www.wm-ophthalmics.com/bestoxol_eye_drops.asp 20. Taurine Eye Drops, Hangzhou East Pharmaceutical Co., Ltd. - [Elektronyy resurs]. - Rezhym dostupu: - http://www.ectrade.com/Auction/FreeSample/361379431/Qingru_Taurine_Eye_Drops.html 21. Taurine Eye Drops, Hubei Kangzheng Pharmaceutical Co., Ltd. [Elektronyy resurs]. - Rezhym dostupu: - http://image.made-in-china.com/2f0j00lvwQiVOhMSpF/Taurine-Eye-Drops.jpg 22. Taurine Eye Drops 0,4g/8ml, AdvaCarePharma - [Elektronyy resurs]. - Rezhym dostupu: - http://www.advacarepharma.com/en/pharmaceuticals/other-preparations/item/441-taurine-eye-drops.html 23. Ushakova L.Y. Voznyknovenye y razvytye syndroma «sukhoho hlaza» u bolʹnykh pervychnoy otkrytouholʹnoy hlaukomoy / L.Y. Ushakova, O.N. Shunkevych // Hlaukoma: teoryy, tendentsyy, tekhnolohyy. HRT/Spectralis Klub Rossyya - 2013: materyaly XI Mezhdunarodnoho konhressa.– M., 2013. – S. 260-264. 24. Basal Tear Turnover and Topical Timolol in Glaucoma Patients and Healthy Controls by Fluorophotometry / Esmeralda V. M. J. Kuppens, Thorsren R. Srolwijk, Rob J. W. de Keizer et. al // Investigative Ophthalmology & Visual Science. - 1992. - Vol. 33, No. 12. – R. 3442 – 3448. 25. Podder S.K. Improving the safety of topically applied timolol in the pigmented rabbit through manipulation of formulation composition / S.K. Podder, V.C. Moy, V.H.L. Lee // Exp. Eye Res. – 1992. – Vol. 54, №5. – P. 747-757. 26. Bioadhesion: The effect of polyacrylic acid on the ocular bioavailability of timolol / F. Thermes, A. Rozier, B. Plazonnet [et al.] // Int. J. Pharm. – 1992. - Vol.81. – R. 59–65. 27. The effect of vehicle viscosity on the ocular bioavailability of L-653,328 / J. Grove , M. Durr , M.P. Quint [et al.] // Int. J. Pharm. - 1990. - Vol. 66, № 1-3. - R. 23-28. 28. Pat. 8501822 SSHA. A61K31/7028; A61R27/02; A61R29/00. Ophthalmic composition containing alginic acid or salt thereof / Matsumoto Eri, Nishina Yasuko, Haruna Kenichi, Arita Harumasa, Kita Akiko, (JP). - №13/431,002; zayavl. 27.03.2012; opubl. 6.08.2013. - 18 r. 29. Different Effects of Absorption Promoters on Corneal and Conjunctival Penetration of Ophthalmic Beta-Blockers / H. Sasaki [et al.] // Pharmaceutical Research. - 1995. - Vol. 2, №8. - R. 1146-1150. 30. Zayava 20100311688 SSHA. A61K31/717; A61R27/04. Ophthalmic formulations, methods of manufacture, and methods of using same / Chapin; Matthew J., Minno George, Nice Jackie, Ousler III George W., Abelson Mark B. (USA). - №12/794315; zayavl. 4.06.2010; opubl. 9.12.2010. - 30 r. 31. Pat. 8450295 SSHA. A61K 31/723; A61K 31/198; A61K 31/145. Ophthalmic composition containing xanthan gum and amino acid / Doi Koji, Aki Hiroshi (JP). - №12/767,185; zayavl. 26.04.2010; opubl. 28.05.2013. - 10 r. 32. Andryukova L.M. Doslidzhennya z standartyzatsiyi farmatsevtychnoyi rozrobky likarsʹkykh preparativ u formi ochnykh krapelʹ: avtoref. dys. na zdobuttya nauk. stupenya dokt. farmats. nauk : spets. 15.00.03 «Standartyzatsiya ta orhanizatsiya vyrobnytstva likarsʹkykh zasobiv» / L.M. Andryukova. - Kharkiv, 2011. - 38 s. 33. Andryukova L.M. Vyznachennya krytychnykh pokaznykiv yakosti likarsʹkoyi formy ochni krapli / L.M. Andryukova, O.H. Fetisova, O.M. Yakubchuk, S.M. Kovalenko // Upravlinnya, ekonomika ta zabezpechennya yakosti v farmatsiyi. - 2013. - № 6. - S. 4-9.